When the Teens Narrate the Selves in Indonesian Literature: Gender, Subject, and Power - Udasmoro, Wening (Lingua Cultura, 2018)
The subjects that participated in the production of meaning in the literature included authors, publishers, and illustrators. The aim of this article was to investigate the role and the exercise of the power of these different subjects in trying to construct teenager identities through teen’s literature in different eras of Indonesia. Different teenager literature was analyzed since The New Order to the Reformasi Era of Indonesian political rule. This research used the Critical Discourse Analysis method, which examined all social and cultural products as discourse. Discourse in this context was the construction that contained within it components that require attention. The analysis shows that there is an environment of gender, middle-and upperclass production, consumption, and the reproduction of narration by those different subjects. All of them compete because they have different agendas. However, they also negotiate and work collaboratively through their own narrations, because they all have the same objective of acquiring financial benefit.